Stylistic Communication Deciphered from Goo Goo Dolls' "Iris" - Ariya Jati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
This essay deals with features of stylistic communication deciphered from Goo Goo Dolls’ Iris. The features are patterned in the text and discourse of the song lyric. The features are patterned as sound devices, process participants and vocabulary communicated within the song lyric. The analysis caters for relationship between grammaticalness and interpretability of the lyric. The analysis is framed within nature of literary communication in stylistics. The pattern creates communication act which is self-contained, independent of social context and expressive of reality.